Notes on the benthic vegetation from the Iberian Peninsula.II. Ulva rigida C. Agardh var. fimbriata J. Agardh in coastal Spain: morphological and anatomical variability - Pérez-Cirera, José Luis; Gallardo, Tomás (Lazaroa, 1981)
The occurrence of Ulva rigida var. fimbriata is reported for the first time from several localities of the NW Spanish coast. A comparison is made to previous descriptions on its morphology and anatomy.